High-thermal-conductivity carbon-based metal heat dissipation piece and preparation method thereof

By mixing carbon high-thermal conductivity material powder with metal high-thermal conductivity material powder and wrapping silicon organic precursors on the surface of the carbon material to form silicon carbide and copper silicon phase layers, the thermal conductivity deficiency in the prior art and The problem of interface thermal fatigue achieves high thermal conductivity and long-life heat dissipation parts.

CN119457074APending Publication Date: 2025-02-18KUNSHAN KADAM NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411596324.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to meet the demand for high thermal conductivity of high performance computing equipment. Traditional pure metal heat dissipation parts lack thermal conductivity, and the interfacial thermal fatigue and impurities of composite materials affect performance.

Method used

The carbon high-thermal conductivity material powder and metal high-thermal conductivity material powder are mixed. By soaking the carbon material powder in the organic precursor of silicon, a silicon carbide layer and a copper-silicon phase layer are formed, thereby improving the bonding relationship and thermal expansion coefficient transition structure. , reduce the chance of crack formation.

Benefits of technology

It significantly improves the thermal conductivity of high-thermal conductivity carbon-based metal heat dissipation parts, extends the service life, and solves the problems of insufficient thermal conductivity and interface thermal fatigue in traditional technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119457074A_ABST
    Figure CN119457074A_ABST
Patent Text Reader

Abstract

According to the preparation method of the high-thermal-conductivity carbon-based metal heat dissipation piece, before the carbon high-thermal-conductivity material powder and the metal high-thermal-conductivity material powder are mixed, the surface of the carbon high-thermal-conductivity material powder is wrapped with the silicon organic precursor in the mode that the carbon high-thermal-conductivity material powder is soaked in the silicon organic precursor and dried, and then the carbon high-thermal-conductivity material powder and the metal high-thermal-conductivity material powder are mixed to form the high-thermal-conductivity carbon-based metal heat dissipation piece. During mixing, the inner wall of mixing equipment is not easily scratched, impurities are not mixed, and during sintering of the subsequent MIM metal injection molding process, on one hand, an organic precursor of silicon reacts with the carbon high-thermal-conductivity material powder to form silicon carbide, and on the other hand, the organic precursor of silicon and the metal high-thermal-conductivity material powder form a silicon alloy phase; a good bonding relationship can be obtained, the connection firmness is improved, and a thermal expansion coefficient transition structure is formed between the two, so that the crack forming probability is reduced, and the thermal conductivity is improved; the high-thermal-conductivity carbon-based metal heat dissipation piece provided by the invention is prepared by adopting the preparation method, and is high in thermal conductivity and long in service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of heat sinks, and in particular to a method for preparing a high thermal conductivity carbon-based metal heat sink and a high thermal conductivity carbon-based metal heat sink. Background Art

[0002] Thermal conductivity is the core parameter of heat sinks. With the continuous growth of high-performance computing technology and big data processing needs, the power density and heat load of key computing components such as GPU, CPU and memory continue to rise. Traditional heat sinks can no longer meet their needs for efficient heat dissipation.

[0003] As we all know, the metal materials that can be used in batches and have high thermal conductivity are silver (420W / mK), copper (400W / mK), and aluminum (247W / mK), with the highest thermal conductivity being 420W / mK. For high-performance computing, the thermal conductivity of its heat sink is generally above 450W / mK. For ultra-high-performance computing, the thermal conductivity of its heat sink needs to exceed 600W / mK. It is difficult to meet the demand by making heat sinks using pure metal. Among non-metals, carbon materials have superb thermal conductivity, such as graphite (800-2000W / mK), diamond (1000-2500W / mK), and graphene (3500-5000W / mK). Therefore, the use of metal and carbon composite materials to prepare high thermal conductivity heat sinks has become an important research direction.

[0004] For example, Chinese patent CN118204491A discloses a diamond and copper-based ultra-high thermal conductivity composite cold plate liquid cooling system part, which uses copper powder and diamond powder as raw materials, and uses MIM metal injection molding process to make heat sinks, which can obtain thin sheets with thermal conductivity as high as 500-800W / mK. However, since copper and diamond do not react by themselves, they need to be mixed for a long time by high shear mixing technology to be uniform. During mixing, the edges and corners of the diamond powder are easy to scratch the inner wall of the mixing equipment, and the scraped debris is mixed into the copper powder and diamond powder, becoming impurities, which will affect the performance of the heat sink. After being made, the interface between the copper and diamond inside the heat sink is clear, without a transition layer, and the thermal expansion coefficient of copper and diamond differs by about 12 times (copper 18.5*10 -6 / ℃, diamond 1.5*10 -6 / ℃), after the heat sink has undergone repeated changes of thermal expansion and contraction, thermal fatigue failure will occur at the interface between copper and diamond, resulting in thermal stress and cracks. The thermal conductivity of such cracks is usually around 0.006-0.7W / mK, which actually becomes a thermal blocking layer, greatly reducing the thermal conductivity of the heat sink. In the article "Research Progress of High Thermal Conductivity Diamond / Copper Composite Materials" published by Li Mingjun et al., the importance of interface modification of composite materials is also emphasized. However, it mainly coats or evaporates trace amounts of metal elements such as titanium, chromium, tungsten, boron, molybdenum, zirconium, etc. on the surface of diamond, and then forms metal carbides after heating reaction. The thermal expansion coefficient of such metal carbides is mostly between 4.4 and 11.7*10 -6 / ℃, which can form a transition between copper and diamond and avoid a sudden change in the coefficient of thermal expansion. When experiencing repeated changes of thermal expansion and contraction, it can improve thermal stress, reduce the probability of crack formation, and increase the service life of the heat sink. However, this solution has a high reaction temperature, high material cost and high process cost. The thermal conductivity of metal carbide itself is generally (17-120W / mK), which is lower than that of diamond and copper itself, which will lower the final thermal conductivity of the heat sink. Summary of the invention

[0005] The purpose of the present invention is to solve one or more shortcomings in the prior art and to provide a method for preparing a high thermal conductivity carbon-based metal heat sink and a high thermal conductivity carbon-based metal heat sink.

[0006] To achieve the above object, the method in the technical solution adopted by the present invention is a method for preparing a high thermal conductivity carbon-based metal heat sink, comprising the following steps:

[0007] a. Using carbon high thermal conductivity material powder with an average particle size D50 of 0.5 microns to 325 microns and metal high thermal conductivity material powder with an average particle size D50 of 5 microns to 30 microns as raw materials;

[0008] b. The carbon high thermal conductivity material powder and the metal high thermal conductivity material powder are mixed evenly to obtain a composite material, wherein the weight fraction of the carbon high thermal conductivity material powder in the composite material is 5wt% to 75wt%;

[0009] c. Adding a binder to the composite material and mixing uniformly to obtain a mixture, wherein the weight of the binder accounts for 8 to 20% of the total weight of the mixture;

[0010] d. Place the mixture in a mixing granulation furnace and heat it to form injection particles with a diameter of 3 to 5 mm;

[0011] e. Injecting the injection molding particles into the preheated mold through the injection molding process, and opening the mold after cooling to obtain the green embryo;

[0012] f. defatting the raw embryo to obtain brown embryo;

[0013] g. Place the brown embryo into a vacuum furnace for sintering, and form a rough embryo of a heat sink with a metallic luster after it is taken out of the furnace;

[0014] h. Grind the size and appearance of the rough blank to obtain a high thermal conductivity carbon-based metal heat sink with mechanical parameters that meet the design requirements;

[0015] Features:

[0016] Before performing step b, the method also includes the step of immersing the carbon high thermal conductivity material powder in the silicon organic precursor and drying it. After drying, the surface of the carbon high thermal conductivity material powder is completely wrapped by the silicon organic precursor. In step g, the silicon organic precursor reacts with the carbon high thermal conductivity material powder to form silicon carbide on the one hand, and forms a silicon alloy phase with the metal high thermal conductivity material powder on the other hand, thereby obtaining a good bonding relationship and forming a thermal expansion coefficient transition structure between the carbon high thermal conductivity material powder and the metal high thermal conductivity material powder, thereby reducing the probability of crack formation and improving the thermal conductivity of the high thermal conductivity carbon-based metal heat sink.

[0017] Preferably, the organic silicon precursor is prepared by using nano-silicon powder through a sol-gel process.

[0018] Further preferably, the organic precursor of silicon is any one of silane coupling agent, bioactive organosilicon, silicone oil, high temperature vulcanized silicone rubber, liquid silicone rubber, silicone resin, silicon tetrachloride, silicon alkoxide or a mixture thereof.

[0019] Further preferably, the general formula of the silane coupling agent is RSiX 3 , wherein R represents amino, vinyl, epoxy, cyano, or methacryloyloxy.

[0020] More preferably, the silane coupling agent is vinyl triethoxysilane, vinyl trimethoxysilane, vinyl tri-β-methoxyethoxysilane, etc.

[0021] Preferably, the carbon high thermal conductivity material powder in step a is any one of diamond powder, graphite powder, graphene powder or a mixture thereof.

[0022] Further preferably, the average particle size D50 of the carbon high thermal conductivity material powder is 0.5 micrometer to 325 micrometer.

[0023] Further preferably, the particle size of the carbon high thermal conductivity material powder is controlled by a three-level grading method, and the proportion of powder of the next order of magnitude particle size is 10% to 30% of the proportion of powder of the previous order of magnitude particle size.

[0024] Preferably, the metal high thermal conductivity material powder in step a is any one of silver powder, copper powder and aluminum powder.

[0025] Further preferably, the average particle size D90 of the metal high thermal conductivity material powder is 5 microns to 8 microns.

[0026] Preferably, the binder in step c comprises 60-90% by weight of polyoxymethylene, 5-35% by weight of polypropylene, 0.5-5% by weight of a heat stabilizer and 0.5-5% by weight of a plasticizer.

[0027] Preferably, the weight ratio of the binder to the carbon high thermal conductivity material powder and the metal high thermal conductivity material powder in step c is 5-30wt%: 10-60wt%: 10-65wt%.

[0028] Preferably, the degreasing in step f is solvent degreasing or catalytic degreasing, and during degreasing, the organic precursor of silicon coated on the surface of the carbon high thermal conductivity material powder is not removed.

[0029] Preferably, the sintering temperature in step g is 900-1200° C., and the sintering is carried out in hydrogen or a protective atmosphere.

[0030] To achieve the above-mentioned purpose, the product in the technical solution adopted by the present invention is a high thermal conductivity carbon-based metal heat sink, which is prepared by the above-mentioned preparation method. The high thermal conductivity carbon-based metal heat sink contains diamond powder and copper powder, the surface of the diamond powder is coated with a silicon carbide layer, and the surface of the copper powder is coated with a copper-silicon phase layer.

[0031] Preferably, the particle sizes of the diamond powder are divided into at least three orders of magnitude, and the diamond powder with smaller particle sizes is distributed in the gaps between adjacent diamond powder with larger particle sizes.

[0032] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0033] The preparation method of the high thermal conductivity carbon-based metal heat sink provided by the present invention, before mixing the carbon high thermal conductivity material powder and the metal high thermal conductivity material powder, the carbon high thermal conductivity material powder is immersed in a silicon organic precursor and dried, so that the surface of the carbon high thermal conductivity material powder is coated with the silicon organic precursor. During mixing, it is not easy to scratch the inner wall of the mixing equipment and no impurities are mixed in. During the subsequent MIM metal injection molding process sintering, the silicon organic precursor reacts with the carbon high thermal conductivity material powder to form silicon carbide on the one hand, and forms a silicon alloy phase with the metal high thermal conductivity material powder on the other hand, so that a good bonding relationship can be obtained, the firmness of the connection can be improved, and a thermal expansion coefficient transition structure can be formed between the carbon high thermal conductivity material powder and the carbon high thermal conductivity material powder, which not only reduces the probability of crack formation, but also can improve the thermal conductivity of the high thermal conductivity carbon-based metal heat sink.

[0034] The high thermal conductivity carbon-based metal heat sink provided by the present invention is prepared by the above-mentioned preparation method, and contains diamond powder and copper powder inside. The surface of the diamond powder is coated with a silicon carbide layer, and the surface of the copper powder is coated with a copper-silicon phase layer. Good bonding can be achieved through the silicon carbide layer and the copper-silicon phase layer to improve the connection firmness, and a transition structure can be formed to reduce the probability of cracks and improve thermal conductivity. The thermal conductivity is high and the service life is long. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a schematic diagram of the connection structure between diamond powder and copper powder in the present invention.

[0036] Figure 2 yes Figure 1 Schematic diagram of the connection between single diamond powder and copper powder.

[0037] Figure 3 It is a schematic diagram of the positions of large-diameter, medium-diameter and small-diameter diamond powders in the present invention.

[0038] Figure 4 It is a schematic diagram of the positions of diamond powder and copper powder in the present invention.

[0039] Among them: (100). Diamond powder; (110). Large-particle diamond powder; (120). Medium-particle diamond powder; (130). Small-particle diamond powder; (150). Silicon carbide layer; (200). Copper powder; (250). Copper-silicon phase layer; (300). Silane coupling agent metal phase. DETAILED DESCRIPTION

[0040] The method for preparing a high thermal conductivity carbon-based metal heat sink provided by the present invention comprises the following steps:

[0041] a. Using carbon high thermal conductivity material powder with an average particle size D50 of 0.5 microns to 325 microns and metal high thermal conductivity material powder with an average particle size D50 of 5 microns to 30 microns as raw materials;

[0042] b. The carbon high thermal conductivity material powder and the metal high thermal conductivity material powder are mixed evenly to obtain a composite material, wherein the weight fraction of the carbon high thermal conductivity material powder in the composite material is 5wt% to 70wt%;

[0043] c. Adding a binder to the composite material and mixing uniformly to obtain a mixture, wherein the weight of the binder accounts for 8 to 20% of the total weight of the mixture;

[0044] d. Place the mixture in a mixing granulation furnace and heat it to form injection particles with a diameter of 3 to 5 mm;

[0045] e. Injecting the injection molding particles into the preheated mold through the injection molding process, and opening the mold after cooling to obtain the green embryo;

[0046] f. defatting the raw embryo to obtain brown embryo;

[0047] g. Place the brown embryo into a vacuum furnace for sintering, and form a rough embryo of a heat sink with a metallic luster after it is taken out of the furnace;

[0048] h. Grind the size and appearance of the rough blank to obtain a high thermal conductivity carbon-based metal heat sink with mechanical parameters that meet the design requirements;

[0049] Before performing step b, the method also includes the step of immersing the carbon high thermal conductivity material powder in the silicon organic precursor and drying it. After drying, the surface of the carbon high thermal conductivity material powder is completely wrapped by the silicon organic precursor. In step g, the silicon organic precursor reacts with the carbon high thermal conductivity material powder to form silicon carbide on the one hand, and forms a silicon alloy phase with the metal high thermal conductivity material powder on the other hand, thereby obtaining a good bonding relationship and forming a thermal expansion coefficient transition structure between the carbon high thermal conductivity material powder and the metal high thermal conductivity material powder, thereby reducing the probability of crack formation and improving the thermal conductivity of the high thermal conductivity carbon-based metal heat sink.

[0050] Preferably, the organic precursor of silicon is prepared using nano-silicon powder through a sol-gel process, and the size effect of nanomaterials (the smaller the particle size, the lower the melting point) can be used to lower the reaction temperature, so as to achieve the technical effect of reacting the organic precursor of silicon with both the carbon high thermal conductivity material powder and the metal high thermal conductivity material powder through sintering in step g. Only one sintering is required, and the sintering temperature is low, which can perfectly cooperate with the densification process after degreasing, thereby producing high thermal conductivity carbon-based metal heat sinks with complex shapes, light, thin, short and small.

[0051] Preferably, the organic precursor of silicon is a silane coupling agent, bioactive organosilicon, silicone oil (silicone grease, silicone emulsion, silicone surfactant), high temperature vulcanized silicone rubber, liquid silicone rubber, silicone resin, silicon tetrachloride (SiCl 4 ), any one of silicon alkoxides or a mixture thereof. Further preferably, the organic precursor of silicon is a silane coupling agent, and its general formula is RSiX 3 , wherein R represents amino, vinyl, epoxy, cyano, or methacryloxy. Furthermore, the silane coupling agent is vinyl triethoxysilane, vinyl trimethoxysilane, vinyl tri-β-methoxyethoxysilane, or the like.

[0052] Preferably, the carbon high thermal conductivity material powder in step a is any one of diamond powder, graphite powder, graphene powder or a mixture thereof. Further preferably, the carbon high thermal conductivity material powder in step a is diamond powder, which has higher upper and lower limits of thermal conductivity than graphite powder, and lower anisotropy than graphene powder, and the effect of improving thermal conductivity is more stable.

[0053] Specifically, the average particle size D50 of the diamond powder is 0.5 micrometers to 325 micrometers. After molding, since the particle size of the diamond powder is larger than that of the metal high thermal conductivity material powder, there are large gaps between adjacent diamond powders, and some of these gaps will be filled with the metal high thermal conductivity material powder, such as Figure 4 As shown, some will not. These unfilled gaps will be filled with silane coupling agent. After sintering, a larger volume of silane coupling agent metal phase will be formed, which will reduce the proportion of diamond, thereby reducing the lower limit of thermal conductivity of high thermal conductivity carbon-based metal heat sink. Therefore, in the present invention, the particle size of diamond powder is preferably controlled by three-level grading, and the proportion of powder of the next order of magnitude particle size is 10% to 30% of the proportion of powder of the previous order of magnitude particle size. After molding, the gaps between adjacent large-particle-size diamond powders will be filled with medium-particle-size diamond powders, and the gaps between adjacent medium-particle-size diamond powders will be filled with small-particle-size diamond powders, thereby increasing the proportion of diamond, so as to exert a better and more stable heat conduction effect and improve the lower limit of thermal conductivity of high thermal conductivity carbon-based metal heat sink.

[0054] Preferably, the metal high thermal conductivity material powder in step a is any one of silver powder, copper powder and aluminum powder. Considering the cost performance, the more preferred solution is copper powder. Furthermore, the particle size D90 of the copper powder is 5 microns to 8 microns.

[0055] Preferably, the binder in step c comprises 80-90% by weight of polyoxymethylene, 5-15% by weight of polypropylene, 0.5-5% by weight of a heat stabilizer and 0.5-5% by weight of a plasticizer.

[0056] Preferably, the weight ratio of the binder to the carbon high thermal conductivity material powder and the metal high thermal conductivity material powder in step c is 5-30wt%: 10-60wt%: 10-65wt%.

[0057] Preferably, the degreasing in step f is solvent degreasing or catalytic degreasing, wherein the temperature of catalytic degreasing is 120-150°C, and the temperature of solvent degreasing is 40-60°C. During degreasing, the organic precursor of silicon wrapped on the surface of the carbon high thermal conductivity material powder is not removed.

[0058] Preferably, the sintering temperature in step g is 900-1200° C., and the sintering is carried out in hydrogen or a protective atmosphere.

[0059] The present invention uses a powder metallurgy injection molding sintering process that is different from traditional casting and dry pressing. It can produce high thermal conductivity carbon-based metal heat sinks with complex shapes and short, small, light, thin, and long shapes. At the same time, it can make the distribution of composite materials more uniform, avoid segregation problems, increase the stability of product performance, and reduce production costs, making it easier to mass produce. The uniform mixing and high-density molding of carbon high thermal conductivity material powder and metal high thermal conductivity material powder are achieved, effectively overcoming the technical difficulties of uneven dispersion and low density in the preparation of high thermal conductivity composite material heat sinks by traditional processes, and can accurately control the shape and size of the product. In particular, it can produce thin sheet materials with a thickness of less than 1 mm, and at the same time, its thermal conductivity can be significantly improved. In addition, the present invention effectively reduces production costs by optimizing the parameters of the MIM injection molding process and selecting more cost-effective raw materials, making it possible to use large-scale composite carbon material powders with high thermal conductivity and metal material powders, thereby meeting the high standard requirements of high-performance electronic devices for heat dissipation materials.

[0060] The following is a description with specific embodiments.

[0061] Embodiment 1

[0062] Materials preparation:

[0063] a. Pure copper powder: Select pure copper powder (200) with good thermal conductivity and an average particle size D50 of 8 to 11 microns, weighing 2000g, to ensure that its purity reaches more than 99.9%.

[0064] b. Diamond powder and pretreatment: Diamond powder (100) with an average particle size D50 of 100 microns and a weight of 1000 g is selected. After calculation, the volume fraction of the diamond powder in the composite material is about 60%; the diamond powder and the silane coupling agent are first mixed evenly according to a weight ratio of 80% and 20%, and then dried.

[0065] c. Prepare a binder according to the weight ratio of polyoxymethylene, polypropylene, compatibilizer and plasticizer: 86%:5%:3%:5%. After preparation, weigh 360g (approximately 11% of the total weight) of the binder.

[0066] d. Preparation of the mixture: Pure copper powder and diamond powder coated with silane coupling agent are put into a high-efficiency mixer filled with inert gas and mixed for 60 minutes until the mixture is completely uniform.

[0067] e. Internal mixing and granulation: The prepared mixture is transferred to a heated and pressurized internal mixing and granulation machine, and specially formulated binders are added in sequence. The temperature of the internal mixing chamber is set to 180°C. After the powder and binder are completely combined and agglomerated, the chamber temperature is lowered to 160°C and the feed is pushed to the pelletizing section via a screw to produce small cylindrical pellets with a diameter of 3*5mm.

[0068] f. Injection molding: Add the prepared feed into the injection molding machine and perform injection molding according to the preset parameters to form the embryo.

[0069] g. Degreasing and sintering: The formed green embryo is placed in a special catalytic degreasing furnace and subjected to oxalic acid degreasing treatment at 120°C for 8 hours to obtain a brown embryo.

[0070] h. High temperature sintering: The degreased brown embryo is transferred to a professional sintering furnace, the furnace temperature is set to 1050℃, and this temperature is maintained for 2 hours for sintering. During the sintering process, 85% hydrogen and 15% nitrogen are injected into the furnace as protective gas to prevent the material from being oxidized or carbonized (diamond carbide) during the sintering process, and an intermediate phase is formed on the carbon base and metal surface, such as Figure 2 shown.

[0071] After the above preparation, a highly thermally conductive carbon-based copper part is obtained, whose thermal conductivity is about 600W / (mK) and has excellent thermal conductivity. The diamond powder is evenly distributed in the pure copper powder matrix and forms a strong physical bond with the pure copper powder, providing a basis for a significant improvement in thermal conductivity.

[0072] Embodiment 2

[0073] The second embodiment is basically the same as the first embodiment, except that the particle size of the diamond powder in the second embodiment is controlled by a three-level grading method, so as to effectively fill the medium-sized diamond particles between the large-sized diamond particles and the small-sized diamond particles between the medium-sized diamond particles, so as to increase the volume percentage of diamond, thereby improving the thermal conductivity of the product. Figure 3 shown.

[0074] Materials preparation:

[0075] a. Pure copper powder: Select pure copper powder with good thermal conductivity and an average particle size D50 of 8 to 11 microns, weighing 2000g, and ensure that its purity reaches more than 99.9%.

[0076] b. Diamond powder and pretreatment: Diamond powders with average particle sizes D50 of 100 microns (110), 10 microns (120) and 1 micron (130) in a ratio of 74:21:5 were selected, with a weight of 1000g. After calculation, the volume fraction of diamond powder in the composite material is about 60%; diamond powder and silane coupling agent are mixed evenly in a weight ratio of 80% and 20%, and then dried.

[0077] c. Prepare the binder: Prepare it according to the weight ratio of polyoxymethylene, polypropylene, compatibilizer and plasticizer: 86%:5%:3%:5%. After preparation, weigh 360g (about 11% of the total weight) of the binder.

[0078] d. Preparation of the mixture: Pure copper powder and diamond powder coated with surfactant are put into a high-efficiency mixer filled with inert gas and mixed for 45 minutes until the mixture is completely uniform.

[0079] e. Internal mixing and granulation: The prepared mixture is transferred to a heated and pressurized internal mixing and granulation machine, and a specially formulated binder is added in sequence. The temperature of the internal mixing chamber is set to 180°C. After the powder and the binder are completely combined and agglomerated, the chamber temperature is lowered to 160°C and the feed is pushed to the pelletizing section via a screw to produce small cylindrical pellets with a diameter of 3*5mm.

[0080] f. Injection molding: The prepared feed is gradually added into the injection molding machine, and injection molding is performed according to preset parameters to form a embryo.

[0081] g. Degreasing and sintering: The green embryo is placed in a special degreasing furnace and degreased with oxalic acid at 120°C for 8 hours to obtain a brown embryo.

[0082] h. High temperature sintering: The brown embryo is transferred to a professional sintering furnace, the furnace temperature is set to 1050℃, and this temperature is maintained for 2 hours. During the sintering process, 85% hydrogen and 15% nitrogen are injected into the furnace as protective gas, and the material is not oxidized or carbonized (diamond carbide) during the sintering process.

[0083] After the above preparation, a highly thermally conductive carbon-based copper part is obtained, whose thermal conductivity is stable at about 640W / (mK) and has excellent thermal conductivity. The diamond powder is evenly distributed in the pure copper powder matrix and forms a strong physical bond with the pure copper powder, providing a basis for a significant improvement in thermal conductivity.

[0084] Embodiment 3

[0085] The main difference from Example 1 is that finer pure copper powder is used, so that the copper powder can be effectively filled between diamond particles to increase the bonding degree of the copper powder and improve its thermal conductivity. Figure 3 shown.

[0086] Materials preparation:

[0087] a. Pure copper powder: Select pure copper powder with good thermal conductivity and an average particle size D90 of 5 to 8 microns, weighing 2000g, and ensure that its purity reaches more than 99.9%.

[0088] b. Diamond powder and pretreatment: Diamond powders with average particle sizes D50 of 100 microns (110), 10 microns (120) and 1 micron (130) in a ratio of 74:21:5 were selected, with a weight of 1000g. After calculation, the volume fraction of diamond powder in the composite material is about 60%; diamond powder and silane coupling agent are mixed evenly in a weight ratio of 80% and 20%, and then dried.

[0089] c. Prepare the binder: Prepare it according to the weight ratio of polyoxymethylene, polypropylene, compatibilizer and plasticizer: 86%:5%:3%:5%. After preparation, weigh 360g (about 11% of the total weight) of the binder.

[0090] d. Preparation of the mixture: Pure copper powder and diamond powder coated with surfactant are put into a high-efficiency mixer filled with inert gas and mixed for 45 minutes until the mixture is completely uniform.

[0091] e. Internal mixing and granulation: The prepared mixture is transferred to a heated and pressurized internal mixing and granulation machine, and a specially formulated binder is added in sequence. The temperature of the internal mixing chamber is set to 180°C. After the powder and the binder are completely combined and agglomerated, the chamber temperature is lowered to 160°C and the feed is pushed to the pelletizing section via a screw to produce small cylindrical pellets with a diameter of 3*5mm.

[0092] f. Injection molding: gradually add the prepared feed into the injection molding machine, and perform injection molding according to preset parameters to form the embryo.

[0093] g. Degreasing and sintering: The green embryo is placed in a special degreasing furnace and degreased with oxalic acid at 120°C for 8 hours to obtain a brown embryo.

[0094] h. High temperature sintering: The brown embryo is transferred to a professional sintering furnace, the furnace temperature is set to 1050℃, and this temperature is maintained for 2 hours. During the sintering process, 85% hydrogen and 15% nitrogen are injected into the furnace as protective gas, and the material is not oxidized or carbonized (diamond carbide) during the sintering process.

[0095] After the above preparation, a highly thermally conductive carbon-based copper part is obtained, whose thermal conductivity is stable at about 680W / (mK) and has excellent thermal conductivity. The diamond powder is evenly distributed in the pure copper powder matrix and forms a strong physical bond with the pure copper powder, providing a basis for a significant improvement in thermal conductivity.

[0096] The high thermal conductivity carbon-based metal heat sink provided by the present invention is prepared by the above-mentioned preparation method. The high thermal conductivity carbon-based metal heat sink contains diamond powder and copper powder. The surface of the diamond powder is coated with a silicon carbide layer, and the surface of the copper powder is coated with a copper-silicon phase layer (such as Cu33Si7, Cu9Si2, Cu15Si4, Cu19Si6). Good bonding can be achieved through the silicon carbide layer and the copper-silicon phase layer to improve the connection firmness. A transition structure can also be formed to reduce the probability of cracks and improve thermal conductivity. The thermal conductivity is high and the service life is long.

[0097] Preferably, the particle sizes of the diamond powder are classified into at least three orders of magnitude, and the diamond powder with smaller particle sizes is distributed in the gaps between adjacent diamond powder with larger particle sizes.

[0098] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high thermal conductivity carbon-based metal heat sink, comprising the following steps: a. Using carbon high thermal conductivity material powder with an average particle size D50 of 0.5 microns to 325 microns and metal high thermal conductivity material powder with an average particle size D50 of 5 microns to 30 microns as raw materials; b. The carbon high thermal conductivity material powder and the metal high thermal conductivity material powder are mixed evenly to obtain a composite material, wherein the weight fraction of the carbon high thermal conductivity material powder in the composite material is 5wt% to 75wt%; c. Adding a binder to the composite material and mixing uniformly to obtain a mixture, wherein the weight of the binder accounts for 8 to 20% of the total weight of the mixture; d. Place the mixture in a mixing granulation furnace and heat it to form injection particles with a diameter of 3 to 5 mm; e. Injecting the injection molding particles into the preheated mold through the injection molding process, and opening the mold after cooling to obtain the green embryo; f. defatting the raw embryo to obtain brown embryo; g. Place the brown embryo into a vacuum furnace for sintering, and form a rough embryo of a heat sink with a metallic luster after it is taken out of the furnace; h. Grind the size and appearance of the rough blank to obtain a high thermal conductivity carbon-based metal heat sink with mechanical parameters that meet the design requirements; Features: Before performing step b, the method also includes the step of immersing the carbon high thermal conductivity material powder in the silicon organic precursor and drying it. After drying, the surface of the carbon high thermal conductivity material powder is completely wrapped by the silicon organic precursor. In step g, the silicon organic precursor reacts with the carbon high thermal conductivity material powder to form silicon carbide on the one hand, and forms a silicon alloy phase with the metal high thermal conductivity material powder on the other hand, thereby obtaining a good bonding relationship and forming a thermal expansion coefficient transition structure between the carbon high thermal conductivity material powder and the metal high thermal conductivity material powder, thereby reducing the probability of crack formation and improving the thermal conductivity of the high thermal conductivity carbon-based metal heat sink.

2. The preparation method according to claim 1, characterized in that: The organic silicon precursor is prepared by using nano silicon powder through a sol-gel process.

3. The preparation method according to claim 2, characterized in that: The organic precursor of silicon is any one of silane coupling agent, bioactive organosilicon, silicone oil, high temperature vulcanized silicone rubber, liquid silicone rubber, silicone resin, silicon tetrachloride, silicon alkoxide or a mixture thereof.

4. The preparation method according to claim 3, characterized in that: The general formula of the silane coupling agent is RSiXR3R, wherein R represents amino, vinyl, epoxy, cyano, or methacryloyloxy.

5. The preparation method according to claim 1, characterized in that: The carbon high thermal conductivity material powder in step a is any one of diamond powder, graphite powder, graphene powder or a mixture thereof, and the average particle size of the carbon high thermal conductivity material powder is 0.5 micron to 325 microns.

6. The preparation method according to claim 5, characterized in that: The particle size of the carbon high thermal conductivity material powder is controlled by a three-level grading method, and the proportion of powder with a particle size of the next order of magnitude is 10% to 30% of the proportion of powder with a particle size of the previous order of magnitude.

7. The preparation method according to claim 1, characterized in that: The metal high thermal conductivity material powder in step a is any one of silver powder, copper powder and aluminum powder, and the average particle size D90 of the metal high thermal conductivity material powder is 5 microns to 8 microns.

8. The preparation method according to claim 1, characterized in that: The degreasing in step f is solvent degreasing or catalytic degreasing. During the degreasing, the organic precursor of silicon wrapped on the surface of the carbon high thermal conductivity material powder is not removed.

9. A high thermal conductivity carbon-based metal heat sink, prepared by the preparation method of claim 1, characterized in that: The high thermal conductivity carbon-based metal heat sink contains diamond powder and copper powder. The surface of the diamond powder is coated with a silicon carbide layer, and the surface of the copper powder is coated with a copper-silicon phase layer.

10. The high thermal conductivity carbon-based metal heat sink according to claim 9, characterized in that: The particle sizes of the diamond powder are divided into at least three orders of magnitude, and the diamond powder with a smaller particle size is distributed in the gaps between the adjacent diamond powders with a larger particle size.

Citation Information

Patent Citations

  • MIM process preparation method of diamond and red copper-based ultrahigh heat conduction composite material and cold plate type liquid cooling heat dissipation system part made of composite material

    CN118204491A